A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic - Carvalho-Filho, Alfredo; Macena, Bruno César Luz; Nunes, Diogo Martins (Zootaxa, 2016)
A new species of Anthiadinae, Odontanthias cauoh, is described from São Pedro and São Paulo Archipelago (SPSPA), Brazil, Equatorial Atlantic. The new species differs from its only Atlantic congener by a combination of several characters: pectoral-fin rays 20; total gill rakers on first arch 39; vomerine tooth patch with a posterior prolongation; pelvic fin not reaching base of last anal-fin ray; dorsal, anal and pelvic fins scaleless; and coloration (dorsal, anal, and pelvic fins mostly dark red). The record of the new species contributes to increase the fish endemism in SPSPA.